The ChlD subunit links the motor and porphyrin binding subunits of magnesium chelatase. Issue 13 (2nd July 2019) - Farmer, David A.; Brindley, Amanda A.; Hitchcock, Andrew; Jackson, Philip J.; Johnson, Bethany; Dickman, Mark J.; Hunter, C. Neil; Reid, James D.; Adams, Nathan B. P.
Abstract : Magnesium chelatase initiates chlorophyll biosynthesis, catalysing the MgATP 2− -dependent insertion of a Mg 2+ ion into protoporphyrin IX. The catalytic core of this large enzyme complex consists of three subunits: Bch/ChlI, Bch/ChlD and Bch/ChlH (in bacteriochlorophyll and chlorophyll producing species, respectively). The D and I subunits are members of the AAA + (ATPases associated with various cellular activities) superfamily of enzymes, and they form a complex that binds to H, the site of metal ion insertion. In order to investigate the physical coupling between ChlID and ChlH in vivo and in vitro, ChlD was FLAG-tagged in the cyanobacterium Synechocystis sp. PCC 6803 and co-immunoprecipitation experiments showed interactions with both ChlI and ChlH. Co-production of recombinant ChlD and ChlH in Escherichia coli yielded a ChlDH complex. Quantitative analysis using microscale thermophoresis showed magnesium-dependent binding ( K d 331 ± 58 nM) between ChlD and H. The physical basis for a ChlD–H interaction was investigated using chemical cross-linking coupled with mass spectrometry (XL–MS), together with modifications that either truncate ChlD or modify single residues. We found that the C-terminal integrin I domain of ChlD governs association with ChlH, the Mg 2+ dependence of which also mediates the cooperative response of the Synechocystis chelatase to magnesium. The interaction site between the AAA + motor and the chelatase domain of magnesium chelatase will be essential for understanding how free energy from the hydrolysis of ATP on the AAA + ChlI subunit is transmitted via the bridging subunit ChlD to the active site on ChlH.